ANALYSIS OF FACTORS CAUSE LOW INFANT IMMUNIZATION ACHIEVEMENTS IN TANJUNGSARI CLINICSANALYSIS OF FACTORS CAUSE LOW INFANT IMMUNIZATION ACHIEVEMENTS IN PUBLIC HEALTH DISTRIC - Juni Kurnia Santi (FORIKES, 2016)
Immunization is a promotif and preventive efforts in basic health services play an important role in the decline of infant mortality that occurs due to a disease that can be prevented by immunization (PD3I). Annual reports from public health Tanjungsari noted that the results of the coverage of immunization activities results of the baby has not yet reached the target UCI (Uneversal Child Immunization). An assumption of the reason for immunization low coverage was the way on how Public Heath Center implemented its management funtion : planning, actuacting (supervision, coordination, cold chain, work load, motivation), evaluating and the result of baby`s immunization program. The risset of study is observational study. tanjunsari Public Health Center district the unit of analysis of this study. The object of study was all immunization program documentation which constituted of planning, implementation, supervision check list, coordination check list, evaluation documents as well as the document of coverage results. The respondent were the personnel of immunization program. The results of study revealed baby`s immunization until four years old is 86% campak, 89% DPT1, 86% DPT3, 87% Polio4, 84% BCG dan 85% HB3. Conclusively, it can derived that was discovered that the coverage of baby`s immunization was far below the UCI (Universal Child Immunization) standart in public health, implementatiton (supervision, coordination, clod chain, load work, motivation) and evaluating immunization program has nor been performed well. The inhibiting factors are now knowledge the process Planning Of Action formulation, no supervision to immunization program dan insufficient motivation to personnel immunization program. Key words : planning, immunization program, Public Health